SOCIAL NETWORKING TECHNOLOGIES IN MEDICINE - Aleksei A. Yakovlev; Vladimir B. Musatov; Larisa V. Glyzhina; Aleksandra Ya. Komarova; Yurii A. Amirkhanyan; Jeffrey A. Kelli (Кубанский научный медицинский вестник, 2019)
The article is a review of Russian and foreign publications on the use of social networking technologies in medicine. The analysis of social networks involves a special methodology that permits communications between the participants of social networks to be studied in a formalized way. The article presents the main terminology and history of the problem, as well as the interpretation of its key definitions (homogeneity, multiplicity, reciprocity/mutuality, bridge, density, distance, clustering coefficient, centrality). It is noted that the methods of social networking analysis are rarely used in the Russian healthcare system, compared to other countries. At the same time, existing social networks have an important impact on health-related behaviour, particularly in terms of contraception, the risk of contracting HIV infection and sexually transmitted diseases, smoking, obesity, physical activity and psychoactive drug consumption. It is important that social networks can be used to accelerate behavioural change, reduce undesirable consequences arising from the spread of negative behaviour, improve social changes and promote innovations. This technology referred to as network interventions, along with its methodology, is described in the present article. In addition, the results of studies into the application of this technology abroad are presented.Conclusion. The use of networking analysis in the domestic healthcare system, focused on Internet communities, can significantly improve the effectiveness of state programs aimed at improving population health.Conflict of interest: the authors declare no conflict of interest.